Identification of flavor generated from irradiation of chicken breast via SPME-GC-MS and GC-IMS - Ying Xu; Yueyan Zhang; Shiqing Song; Lingyun Yao; Min Sun; Huatian Wang; Chuang Yu; Qian Liu; Jun Lu; Tao Feng (Journal of Future Foods)
Irradiation as a cold sterilization technology is increasingly used in chicken breast. The odor of animal food produced by medium dose irradiation is rarely reported. The purpose of this study was to investigate the effect of irradiation intensity on the distribution of volatile compounds in chicken breast, and to provide the appropriate irradiation methods for reference to decontamination of chicken breast in practice. The volatiles in chicken breast at different irradiation doses were investigated by headspace solid-phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS) and GC-ion mobility spectrometry (GC-IMS). There were 91 aroma compounds identified in this study, including 12 esters, 13 ketones, 15 aldehydes, 14 alcohols and so on. The volatiles in the irradiated chicken breasts were different from those in the non-irradiated chicken breasts. Sensory evaluation was conducted on irradiated chicken breasts, and partial least squares regression (PLSR) analysis was performed in combination with the volatile compound concentration to identify the characteristic compounds that contributed significantly to the fruity, musty, greasy, chicken flavor and paint flavor. It was indicated that (E)-2-octenal (odor activity value: 0.13−2.13), 1-octen-3-ol (7.66−113.44), nonanal (3.03−215.35), and acetoin (0.85−1.43) might be the characteristic compounds for irradiate-generated off-flavors. The irradiation intensity of 4 and 6 kGy had little negative effect on the flavor of chicken breast. In practical application, the irradiation dose of 4−6 kGy can be selected. Our study provided a reference for the selection of irradiation intensity in the processing of chicken breast, and revealed that the volatile substances had a great influence on the flavor of irradiated chicken breast, which laid a foundation for subsequent flavor regulation.